Solving the RNA polymerase I structural puzzle. (1st October 2014) - Moreno‐Morcillo, María; Taylor, Nicholas M. I.; Gruene, Tim; Legrand, Pierre; Rashid, Umar J.; Ruiz, Federico M.; Steuerwald, Ulrich; Müller, Christoph W.; Fernández‐Tornero, Carlos
<x xml:space="preserve">Abstract</x> Knowing the structure of multi‐subunit complexes is critical to understand basic cellular functions. However, when crystals of these complexes can be obtained they rarely diffract beyond 3 Å resolution, which complicates X‐ray structure determination and refinement. The crystal structure of RNA polymerase I, an essential cellular machine that synthesizes the precursor of ribosomal RNA in the nucleolus of eukaryotic cells, has recently been solved. Here, the crucial steps that were undertaken to build the atomic model of this multi‐subunit enzyme are reported, emphasizing how simple crystallographic experiments can be used to extract relevant biological information. In particular, this report discusses the combination of poor molecular replacement and experimental phases, the application of multi‐crystal averaging and the use of anomalous scatterers as sequence markers to guide tracing and to locate the active site. The methods outlined here will likely serve as a reference for future structural determination of large complexes at low resolution.